Հայաստանի Հանրապետութեան եւ Ծոցի արաբական երկրների միջեւ տնտեսական կապեր.ռիսկեր ու հնարաւորութիւններ - Մնացականեան, Վիլէն (տպ. Atlas)
Cooperation between Armenia and the Arab world has deep historical roots, but nowadays a significant part of the potential of this relationship has not yet been realized. The research is aimed at finding out the current level of existing relations in terms of both trade turnover and investment attraction. First of all, the author emphasizes the high level of concentration in existing relationships: on the one hand, it is expressed by the significant dominant role of the United Arab Emirates in the relations, on the other hand, by the sale of one or two products in the commodity structure of the trade turnover.
Keywords: Տնտեսագիտութիւն